P35-F Brainstem auditory evoked potentials in patients with primary Sjögren's syndrome. Issue 7 (July 2019) - Prosół, Marta Waliszewska; Sebastian, Agata; Dziadkowiak, Edyta; Wiland, Piotr; Budrewicz, Sławomir; Ejma, Maria
Abstract : Background: Primary Sjögren's syndrome (pSS) is a chronic autoimmune exocrinopathy characterized by dysfunction of exocrine glands. Central nervous system (CNS) involvement is estimated to be present in 3–60% patients with pSS. The aim of our study was to evaluate parameters of brainstem auditory evoked potentials (BAEP) in pSS patients without clinical neurological deficit, and without otolaryngological abnormalities. Material and methods: 36 patients with pSS (35 women, 1 man, mean age 49.3 years old) and 40 healthy controls, sex and age-matched were studied. They did not suffer from disease that could have affected the brain electrical activity. Clinical neurological and otolaryngological examinations, laboratory parameters (C3 and C4 component, ANA antibodies, RF levels), brain imaging (CT or MRI) and BAEP were performed. Statistical analysis was performed using the Statistica 10.0 PL software. Results: In none of the patients were the abnormalities on brain imaging found. Abnormal BAEP were recorded in 6 patients (16.6%). pSS patients had a longer mean wave I and V latency and mean wave III-V and I-V interpeak latencies than the controls. There were no correlations between BAEP parameters and laboratory tests. Conclusions: 1. In pSS patients without clinical central nervous system impairment the auditory pathway disturbances could be found. 2. Disorders of the brain bioelectrical activity in the course of pSS may be associated with an ongoing autoimmune process. item The analysis of BAEP may be useful methods of assessment of the CNS in patients without clinical neurological symptom.